Tumor-derived miR-378a-3p-containing extracellular vesicles promote osteolysis by activating the Dyrk1a/Nfatc1/Angptl2 axis for bone metastasis. (1st February 2022) - Wang, Jialin; Du, Xinxing; Wang, Xiao; Xiao, Huixiang; Jing, Nan; Xue, Wei; Dong, Baijun; Gao, Wei-Qiang; Fang, Yu-Xiang
Abstract: Most prostate cancer (PCa)-related deaths are caused by progression to bone metastasis. Recently, the importance of extracellular vesicles (EVs) in pre-metastatic niche formation has been reported. However, whether and how tumor-derived EVs interact with bone marrow macrophages (BMMs) to release EV-delivered microRNAs to promote osteolysis and induce pre-metastatic niche formation for PCa bone metastasis remain unclear. Our in vitro and in vivo functional and mechanistic assays revealed that EV-mediated release of miR-378a-3p from tumor cells was upregulated in bone-metastatic PCa, maintaining low intracellular miR-378a-3p concentration to promote proliferation and MAOA-mediated epithelial-to-mesenchymal transition. Moreover, miR-378a-3p enrichment in tumor-derived EVs was induced by hnRNPA2B1 (a transfer chaperone) overexpression. After tumor-derived EVs were taken in by BMMs, enriched miR-378a-3p promoted osteolytic progression by inhibiting Dyrk1a to improve Nfatc1 (an osteolysis-related transcription factor) nuclear translocation, to activate the expression of downstream target gene Angptl2. As a feedback, increased Angptl2 secretion into the tumor environment promoted PCa progression. In conclusion, tumor-derived miR-378a-3p-containing EVs play a significant role in PCa bone metastasis by activating the Dyrk1a/Nfatc1/Angptl2 axis in BMMs to induce osteolytic progression, making miR-378a-3p a potential predictor of metastatic PCa. Reducing the release of miR-378a-3p-containing EVs or inhibiting the recruitment of miR-378a-3p into EVs can be a therapeutic strategy against PCa metastasis. Highlights: EV-mediated miR-378a-3p release is elevated in bone-metastatic prostate cancer. A low intracellular miR-378a-3p level promotes proliferation and EMT in cancer cell. Intake of miR-378a-3p in BMMs promotes osteolysis by Dyrk1a/Nfatc1 pathway. MiR-378a-3p induced osteolysis increases secretion of Angptl2 for tumor progression.